Immunogenicity of Potential CD4+ and CD8+ T Cell Epitopes Derived From the Proteome of Leishmania braziliensis - e Silva, Rafael de Freitas; de Oliveira, Beatriz Coutinho; da Silva, Ailton Alvaro; Brelaz de Castro, Maria Carolina Accioly; Ferreira, Luiz Felipe Gomes Rebello; Hernandes, Marcelo Zaldini; de Brito, Maria Edileuza Felinto; de-Melo-Neto, Osvaldo Pompílio; Rezende, Antônio Mauro; Pereira, Valéria Rêgo Alves (Frontiers in Immunology, 2020)
Background A safe and effective vaccine against human leishmaniasis still requires the identification of better antigens for immunization and adequate models to evaluate the immune response. To support vaccine development, this work tested the immunogenicity of ten different peptides derived from the proteome of Leishmania braziliensis, which were selected by their in silico affinity to MHC complexes. Research design and methods Comparative cell proliferation assays were performed by culturing, in the presence of each peptide, PBMC cells from subclinical subjects (SC), cutaneous leishmaniasis patients with active disease (AD), post-treatment (PT) individuals, and healthy controls. Culture supernatants were then used for Th1, Th2 and Th17 cytokine measurements. Cells from selected PT samples were also used to assess the expression, by T cells, of the T-bet Th1 transcription factor. Results A robust cell proliferation was observed for the SC group, for all the tested peptides. The levels of Th1 cytokines were peptide-dependent and had substantial variations between groups, where for instance IFN-γ and TNF levels were some of the highest, particularly on PT cultures, when compared to IL-2. On the other hand, Th2 cytokines displayed much less variation. IL-6 was the most abundant amongst all the evaluated cytokines while IL-4 and IL-10 could be found at much lower concentrations. IL-17 was also detected with variations in SC and AD groups. T-bet was up-regulated in CD4+ and CD8+ T cells from the PT group after stimulation with all peptides. Conclusions The peptide epitopes can differentially stimulate cells from SC, AD and PT individuals, leading to distinct immune responses.